2024
DOI: 10.3390/ijms25031778
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of White- and Red-Fleshed Apple Fruits Uncovered Novel Genes Related to the Regulation of Anthocyanin Biosynthesis

Sylwia Keller-Przybylkowicz,
Michal Oskiera,
Xueqing Liu
et al.

Abstract: The red flesh coloration of apples is a result of a biochemical pathway involved in the biosynthesis of anthocyanins and anthocyanidins. Based on apple genome analysis, a high number of regulatory genes, mainly transcription factors such as MYB, which are components of regulatory complex MYB-bHLH-WD40, and several structural genes (PAL, 4CL, CHS, CHI, F3H, DFR, ANS, UFGT) involved in anthocyanin biosynthesis, have been identified. In this study, we investigated novel genes related to the red-flesh apple phenot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In addition, in a poplar heat stress response experiment, a 6 h genome-wide gene expression analysis of heat stress identified 29,898 differentially expressed genes that interact to regulate the expression of photosynthesis-related genes in response to heat stress and control carbon fixation [40]. Transcriptomic analysis of whiteand red-meat apples also revealed a new gene regulating fruit color, UFGT, which is directly responsible for anthocyanin accumulation during apple ripening [41]. In this study, the KEGG enrichment results showed that there were 16 differentially expressed genes related to the expression of photosynthetic antenna protein genes in PSI and PSII.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a poplar heat stress response experiment, a 6 h genome-wide gene expression analysis of heat stress identified 29,898 differentially expressed genes that interact to regulate the expression of photosynthesis-related genes in response to heat stress and control carbon fixation [40]. Transcriptomic analysis of whiteand red-meat apples also revealed a new gene regulating fruit color, UFGT, which is directly responsible for anthocyanin accumulation during apple ripening [41]. In this study, the KEGG enrichment results showed that there were 16 differentially expressed genes related to the expression of photosynthetic antenna protein genes in PSI and PSII.…”
Section: Discussionmentioning
confidence: 99%